2017
DOI: 10.1177/0954410017717756
|View full text |Cite
|
Sign up to set email alerts
|

Finite time fault-tolerant attitude control for rigid-flexible coupling satellites based on Legendre neural network

Abstract: This paper investigates the finite time fault-tolerant attitude control for rigid-flexible coupling satellites in large angle rapid maneuver when some of the actuators are in the fault condition. Based on the first-order approximate method, a more accurate dynamic model for rigid-flexible coupling satellites is set up. Then, Legendre polynomial-based neural network is introduced to estimate the lump perturbation including the estimation error of the fault control torque, high-order flexible coupling terms, ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…However, the convergence rate of standard state observer based on linear feedback is exponential. In order to get the finite time state observer, integrate (1) on both sides dt + + = − ∫  η η K η δω (13) Define ζ and y as follows…”
Section: Finite Time State Observermentioning
confidence: 99%
“…However, the convergence rate of standard state observer based on linear feedback is exponential. In order to get the finite time state observer, integrate (1) on both sides dt + + = − ∫  η η K η δω (13) Define ζ and y as follows…”
Section: Finite Time State Observermentioning
confidence: 99%
“…Additionally, some studies have involved fault-tolerant attitude control in which reaction wheels are used to control satellites for different purposes while considering various constraints like saturation, redundancy, flexibility, angular velocity knowledge, or fault information. 20,[186][187][188][189][190][191][192] Furthermore, it was shown that different selections of attitude sensors could affect the necessity of an active FTC. For example, Wang et al 193 proposed an adaptive fault-tolerant attitude control system for the rigid body satellite affected by actuator faults, space environmental disturbances, and several system uncertainties.…”
Section: Fault-tolerant Controlmentioning
confidence: 99%
“…Similarly, there are some studies on the faulttolerant attitude control of satellites using reaction wheels for different goals and considering various constraints like saturation, redundancy, flexibility, angular velocities knowledge, or fault information. [7][8][9][10][11][12][13][14] One of the other challenges in modern missions, like missions with high power payloads, is the demand for large appendages, like solar panels. [15][16][17] Also, the size constraints of launching and injecting the spacecraft into orbit leave the deployable solar panels a considerable choice.…”
Section: Introductionmentioning
confidence: 99%
“…20 The core model of a satellite with flexible panels in the mentioned articles is based on the represented model of Monaco and Stornelli 19 and used without validation. On the other hand, most of the other studies just assume a fixed and bounded error in the moment of inertia and proposed an FTC [7][8][9][21][22][23][24][25][26][27] with different goals and control methods.…”
Section: Introductionmentioning
confidence: 99%